Achromatopsia. Issue 5 (July 2015) - Remmer, Meredith H.; Rastogi, Neelesh; Ranka, Milan P.; Ceisler, Emily J.
<x xml:space="preserve">Abstract</x> Purpose of review The purposes of this article are to examine the literature published on achromatopsia and provide a comprehensive review of the clinical disease, genetic characteristics, and potential for therapy. Specifically, this article will describe recent advances in gene therapy in animal models, clinical features in human, and barriers to human translation. Recent findings Building on prior success with adeno-associated virus (AAV) therapy in mice models for achromatopsia with mutations in the CNGB3, CNGA3, or GNAT2 genes, multiple cone-specific promoters have recently been developed and shown success in mice and nonhuman primates. A sheep CNGA3 model has also been characterized. Two clinical trials are under way: one to better characterize humans with achromatopsia and another to study a ciliary neurotrophic factor (CNTF) implant as a treatment for patients with the CNGB3 mutation. Summary Genetic understanding and disease characterization of achromatopsia continues to evolve, as do gene therapy tools and animal models. The potential for the treatment of achromatopsia in humans with gene therapy shows great promise.